2022
DOI: 10.3389/fpls.2022.870876
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Heterophylly: Single and Multi-Leaf Genome-Wide Association Mapping in Populus euphratica

Abstract: Heterophylly is an adaptive strategy used by some plants in response to environmental changes. Due to the lack of representative plants with typical heteromorphic leaves, little is known about the genetic architecture of heterophylly in plants and the genes underlying its control. Here, we investigated the genetic characteristics underlying changes in leaf shape based on the model species, Populus euphratica, which exhibits typical heterophylly. A set of 401,571 single-nucleotide polymorphisms (SNPs) derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…It should be noted that our study also identified some other key genes through GWAS and WGCNA analyses, such as cytochrome P450 ( Bp07g0752 , Bp07g0237 ), WD repeat-containing protein ( Bp02g0499 ), UDP-glycosyltransferase ( Bp08g0037 ), and serine/threonine-protein kinase ( Bp05g0658 ), which might also be involved in the regulation of heterophylly in woody plants. Consistent with this view, the previous GWAS analysis in P. euphratica also identified significant genes associated with heterophylly, which encoded WD repeat-containing protein, serine/threonine-protein kinase [ 23 ], and cytochrome P450 [ 22 ]. Moreover, this study identified a series of DEGs encoding KNOX, TCP, CUC, BEL, and Dof transcription factors, which are also important for leaf development and heterophylly of plants.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…It should be noted that our study also identified some other key genes through GWAS and WGCNA analyses, such as cytochrome P450 ( Bp07g0752 , Bp07g0237 ), WD repeat-containing protein ( Bp02g0499 ), UDP-glycosyltransferase ( Bp08g0037 ), and serine/threonine-protein kinase ( Bp05g0658 ), which might also be involved in the regulation of heterophylly in woody plants. Consistent with this view, the previous GWAS analysis in P. euphratica also identified significant genes associated with heterophylly, which encoded WD repeat-containing protein, serine/threonine-protein kinase [ 23 ], and cytochrome P450 [ 22 ]. Moreover, this study identified a series of DEGs encoding KNOX, TCP, CUC, BEL, and Dof transcription factors, which are also important for leaf development and heterophylly of plants.…”
Section: Discussionsupporting
confidence: 53%
“…To adapt to the changeable environment, plants have formed a variety of adaptive strategies; altering leaf morphology is one of the important adaptation mechanisms for heterophyllous plants [ 27 , 28 ]. Although heterophylly has been the subject of a preliminary study in aquatic and amphibian plants [ 6 , 10 ], the genetic basis for eco-adaptability of heterophyllous leaves is still unclear in terrestrial woody plants, and the relevant studies were mainly carried out in Populus euphratica [ 22 , 24 , 29 ]. To further clarify the mechanisms underlying heterophylly in woody plant species, we systematically and comprehensively evaluated the variation of heterophyllous leaves in a natural population of paper mulberry, which exhibits significant heterophylly and eco-adaptability [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation